Complete cardiac and bronchial avulsion in a dog: Post-mortem computed tomography and forensic necropsy analysis - Campos Fonseca Pinto, Ana Carolina Brandao de; Rodrigues Massad, Mara Rita [UNESP]; Ribas, Laila Massad [UNESP]; Baroni, Carina Outi; Tremori, Talia Missen [UNESP]; Jacinto Reis, Servio Tulio [UNESP]; Rocha, Noeme Sousa [UNESP] (Elsevier B.V., 2017)
The aim of this case report was to describe non-contrast tomography findings of a cardiovascular trauma followed by a forensic necropsy in a dog. A female dog was struck by a vehicle, suffered a sudden death and was sent to a veterinary hospital. PMCT images were acquired on a 16-slice multidetector scanner and the forensic necropsy was performed afterwards. Thoracic images revealed aorta avulsion, heart dislocation, complete right bronchial rupture, pneumothorax, pleural effusion, subcutaneous emphysema, multiple rib and spine processes fractures, and a diaphragmatic rupture. Abdominal images showed free abdominal fluid, and laceration of the abdominal muscles leading to eventration of small bowel. Forensic necropsy findings corroborated the hypothesis of cardiac and bronchial avulsion. Even though no contrast media was administered in this case, it was possible to establish the cause of death based solely on the PMCT images. Further studies in this field should be conducted to evaluate the capabilities of PMCT in improving post-mortem diagnosis or even replacing it when necessary.
Keywords: Forensic science; Forensic pathology; Forensic radiology; Post-mortem diagnosis; Aorta; Cardiac trauma